Analysis of the incidence of Musculoskeletal Disorder in Weaving Workers at the Ulos Sianipar Gallery - Rina Khairuna Nasution; Syafran Arrazy (International Archives of Medical Sciences and Public Health, 2020)
Introduction: Galery Ulos Sianipar is an ulos and songketmanufacturing company. Ulos are created in this gallery on a nonmachine loom that is operated with the feet and hands, and theweaving activity is carried out continuously while sitting.Musculoskeletal disorders can develop as a result of weaving work(MSDs). The purpose of this study was to ascertain the factors thatcontribute to musculoskeletal disorder complaints among weavingworkers at Galery Ulos Sianipar. Method: This is a quantitativestudy conducted in a cross-sectional fashion. This study enrolled 32individuals. Purposive sampling is a sampling technique used. TheNordic Body Map (NBM) was used to assess musculoskeletalcomplaints; the Rappid Upper Limb Assessment was used to assesswork posture (RULA). Fisher's exact test was used in the bivariatetest. Result : The findings indicated that 24 respondents (75%) hadmild MSDs, while 8 respondents (25%) had severe MSDs. Thebivariate analysis revealed a relationship between physical fitnessand MSD complaints (p=0.038). There is no correlation betweenMSD complaints and age (p-value = 0.625), years of service (p-value= 1,000), or work posture (p-value = 0.176). Conlusion Weavers areencouraged to adopt a more upright posture and participate in sportsand stretches prior to, during, and after work.